Censorship detected in SN (Senegal) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Senegal. Data sourced from OONI.
Censorship Incident ID: SN-2026-0016. Severity: critical. Confidence: 86%